Synthesis of 6′‐Methyl‐2′‐O, 4′‐C‐methylene‐α‐L‐ ribofuranosyl‐pyrimidine Nucleosides. Issue 11 (20th March 2019) - Mangla, Priyanka; Maity, Jyotirmoy; Rungta, Pallavi; Verma, Vineet; Sanghvi, Yogesh S.; Prasad, Ashok K.
Abstract: Herein, we report the efficient synthesis of (6′ R )‐ and (6′ S )‐6′‐methyl‐2′‐ O, 4′‐ C ‐methylene‐ α ‐L‐ribofuranosyl‐thymine, and (6′ R )‐ and (6′ S )‐6′‐methyl‐2′‐ O, 4′‐ C ‐methylene‐ α ‐L‐ribofuranosyl‐uracil starting from diacetone glucofuranose in overall yields of 6.3, 4.7, 5.4 and 4.0%, respectively. The key step in the synthesis of stereochemically defined 6′‐Me‐bicyclic‐nucleosides is the nucleophilic addition of methyl group at methylene carbon of 4‐ C– CH2 OH moiety of the 4‐ C ‐ tert ‐butyldiphenylsilyloxymethylated sugar precursor. Thus, the methyl group was added on the aldehyde obtained from Dess‐Martin periodinane oxidation of the precursor alcohol employing AlMe3 in hexane. Both (6′ R )‐ and (6′ S )‐stereoisomers of bicyclic nucleosides T and U were successfully synthesized following Vorbrüggen nucleobase coupling of T and U with triacetylated glycosyl donor obtained from acetolysis of (5 R )‐ and (5  S )‐4‐ C ‐( tert ‐butyldiphenylsilyloxymethyl)‐5‐ C ‐methyl‐1, 2‐ O ‐isopropylidene‐3‐ O ‐(2‐naphthylmethyl)‐ α ‐D‐xylofuranoses and further cyclization and deprotection of the resulted nucleoside. One of the nucleosides, (6′ R )‐6′‐methyl‐2′‐ O, 4′‐ C ‐methylene‐ α ‐L‐ribofuranosyl‐uracil has been reported earlier in 1.8% yield, while the present methodology yielded the nucleoside in 5.4% yield. All the synthesized 6′‐Me‐bicyclic‐nucleosides showed no significant anti‐viral activity against H1 N1 strain of influenza A virus (A/Puerto Rico/8/1934). Abstract : The stereochemically defined (6′ R )‐ and (6′ S )‐6′‐methyl‐2′‐ O, 4′‐ C ‐methylene‐ α ‐L‐ribofuranosyl‐thymine, and (6′ R )‐ and (6′ S )‐6′‐methyl‐2′‐ O, 4′‐ C ‐methylene‐ α ‐L‐ribofuranosyl‐uracil have been synthesized using low cost commercially available starting material, diacetone glucofuranose via nucleophilic addition of Me‐group at methylene carbon of 4‐ C– CH2 OH moiety of the 4‐ C ‐ tert ‐butyldiphenylsilyloxymethylated sugar precursor. The antiviral activity of synthesized 6′‐methylbicyclic‐nucleosides was tested against H1N1 strain of influenza A virus (A/Puerto Rico/8/1934) and found that these compounds are not active.